Beyond distance learning. Communication and visual education between school and family - Cortoni, Ida (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The emergent state of Covid-19 has had a strong impact in the field of education, with particular reference to distance learning, so much so that the uses of digital technology and its applications are now an essential topic in public and political debate. The implementation of distance learning, in fact, has necessarily led to a reflection on the methodological paths that can be applied and tested in the educational context, where new modes of relationship/ interaction, as well as new stimuli for learning, are among the best practices to be adopted to respond to the socio-cultural and educational context that is taking shape, also with reference to doing school. There are many uncertainties linked to the validity of new digital didactic approaches and to the communicative and transmissive effectiveness of the contents where the digital skills of teachers and families and the lack of adequate equipment risk compromising the objective of effective and inclusive education. Among the critical issues that have emerged is that of guaranteeing, through the digital medium, participatory, motivating and engaging teaching for students, capable of increasing their sense of responsibility for self-learning and their emotional involvement in interaction. A new educational media design is called upon to respond to the new digital challenges. How can educational quality and inclusion be guaranteed through digital communication, beyond socio-cultural inequalities? How can school digital capital guarantee new educational planning in the classroom? These are the main questions of the paper, which will focus on illustrating the communicative strategies of visual storytelling and graphicacy as tools for democratising digital communication, for sociocultural inclusion and for reducing sociocultural inequalities, by illustrating the structural framework and the main actions/strategy of the European Erasmus Plus project CAVE (Communication and Visual Education in homeschooling).